Kalaborasi Orang Tua Dan Anak Dalam Mengedit Konten "Analisis Konten Kreatif Di Tiktok" - Asqia, Nurul; Wahyuni, Sri (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Tiktok has become a place for children to express themselves, share ideas, and find new communities. With various challenges, trends, and creative content that continue to emerge, TikTok has become a medium that is both entertaining and educational. So that they are not just consumers of social networking products, children must be invited to be active as content creators that are appropriate for their age. This can also be a way for children to have more direct interaction with their parents rather than being busy with their devices. This research uses library research methods. The research results show that if parents are involved in TikTok content, children can create fun moments strengthen family closeness and can also foster self-confidence, and improve children's cognitive development, language, artistic skills, and creativity. So that they are not just consumers of social networking products, children must be invited to be active as content creators that are appropriate for their age.